"Exploring the Legacy: Chinese Monk Translators in Historical Context" - Rukwal, Brijeshwari (जम्बूद्वीप - the e-Journal of Indic Studies (ISSN: 2583-6331), 2024)
Abstract: About the seventh century CE, when Europe was still in dark ages, India and China lived an intense political, Intellectual, religious and artistic life. The common bond created between them by Buddhism generated a great current of humanism which spread from Sri Lanka to Japan Faxian returned Back to China after about eleven years, the rest of his life was dedicated by himself to the translations of the Buddhist texts brought from India. It is said that once Faxian went southward after his arrival in China from India and a local chief requested him not to go southwards because it was chilly winter time, he requested Faxian to wait up to winters are over on this Faxian responded like, ‘I have devoted my life to Buddhism and spread and development of Buddhism, this was the reason behind my dangerous journey to India. And now I am going to South to request learnt Indian Buddhist scholar Buddhabhadra to assist me in the translations of the texts I have collected from India with great efforts. So don’t stop me as my mission and duty towards Lord Buddha and his Dhamma is yet incomplete.’ Then in spite of bad weather Faxian travelled to Jiankang and invited Buddhist master from India Buddhabhadra to accompany him in translations and editing of various Buddhist texts from Sanskrit to Chinese. Along with Buddhabhadra he translated ‘Mahapariniravanasutta, Mahasamaghika Vinaya, and Samyuktabhidharmahrdaya sastra etc. The Chinese version of Mahapariniravanasutta was widely spread. Xuanzang was born in a family of scholars in Henan province of China. He came to India without any official permission from the Government of China he was chased by an arrest-warrant by the Chinese Government for violation of the ban of travelling abroad. But to the surprise when he reached back to China he was received with a great honor and was given a grand red carpet reception by the Chinese emperor. He has translated few Taoist texts into Sanskrit at the request of the Bhaskaravarmana, the king of Kamarupa. The Taoist text he translated is called ‘Daodejing’. No doubt Xuanzang had been disappointed and pained when he saw the ignorance and lack of knowledge about China and Chinese philosophy among the Indians. He probably have translated the Taoist text into Sanskrit to introduce in India the rich philosophy and culture of China. But unfortunately this Sanskrit translation of ‘Daodejing’ is lost to us. During the time of Xuanzang the Buddhism was well established in China. He had developed a nice command on the Vijnanavada i.e. the treatises of epistemology particularly the Mahayana-samagraha i.e. the ‘Compendium of Mahayana’ of Asanga which had already been translated into Chinese. At his return to China he too devoted his life in translations of Sanskrit Buddhist texts into Chinese. It will be mentioned here that we have lost original copies of some of those texts but thanks to Xuanzang that now we can restore those from his translations. Keywords: Chinese, Sanskrit,Xuanzang, Faxian,Vignanavada .